1999
DOI: 10.1159/000017397
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Development in Benign Focal Epilepsies of Childhood

Abstract: Benign focal epilepsy of childhood (BFEC) is the most common form of epilepsy, in children from 3 to 12 years. Its prognosis is always favourable as far as the epilepsy is concerned. Nevertheless, recent clinical data suggest that children affected by BFEC are more likely to show learning difficulties and behavioural disturbances than their peers. We report here the preliminary findings of a prospective study of 22 children affected with BFEC. Electroclinical and neuropsychological changes observed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
0
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 25 publications
7
137
0
11
Order By: Relevance
“…Earlier studies disclosed that the disruptive effect of a single IED is directly proportional to the voltage of the wave but not the spike (Shewmon and Erwin, 1988c). This observation and the direct relationship between the spatio-temporal amount of the spikewave series and the severity of the deficit symptoms in the long run (Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001) are independently derived findings but lead to the same conclusion: the greater the degree of neuronal synchronization over time and space the greater the cortical dysfunction. As to avoid confusion in this paper "synchronization" refers to the synchronous activation of great cortical neuronal masses (Nunez, 1995), the result of which is reflected by the increase of the voltage of the EEG signal (Pfurtscheller and Lopes da Silva, 1999).…”
Section: The Importance and The Assessment Of "Synchronization"mentioning
confidence: 87%
See 1 more Smart Citation
“…Earlier studies disclosed that the disruptive effect of a single IED is directly proportional to the voltage of the wave but not the spike (Shewmon and Erwin, 1988c). This observation and the direct relationship between the spatio-temporal amount of the spikewave series and the severity of the deficit symptoms in the long run (Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001) are independently derived findings but lead to the same conclusion: the greater the degree of neuronal synchronization over time and space the greater the cortical dysfunction. As to avoid confusion in this paper "synchronization" refers to the synchronous activation of great cortical neuronal masses (Nunez, 1995), the result of which is reflected by the increase of the voltage of the EEG signal (Pfurtscheller and Lopes da Silva, 1999).…”
Section: The Importance and The Assessment Of "Synchronization"mentioning
confidence: 87%
“…However, other investigators described fluctuating neurological symptoms, disturbed speech and cognitive impairment that were related to the presence of frequent IEDs but not strictly time-locked to them. Drug treatment that abolished the spikes caused significant clinical improvement within a short time period (Hirsch et al, 1990;Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001;Dalla Bernardina et al, 2002). Thus, a "delayed effect" of the IEDs might be deductively postulated as an explanation for the lack of the precise temporal coincidence between the IEDs and the time course of the above mentioned symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Vigilance was not impaired in the clinical subjects. An increased distractibility, impulsiveness and hyperactivity were often reported (Giordani et al, 2006;Massa et al, 2001;Metz-Lutz et al, 1999;Volkl-Kernstock et al, 2009). Holtmann et al (2006) administered a neuropsychological battery focusing on attentional processing, cognitive efficiency, response inhibition, visuo-spatial and verbal short-term memory and language functions in 16 children with ADHD and BECTS, 16 with ADHD but no EEG discharges, and 16 healthy controls.…”
Section: Neuropsychological and Behavioral Profilementioning
confidence: 96%
“…Deltour et al (2007) found that children with an earlier onset of seizures made more omission errors and had slower reaction times in the Continuous Performance Test. Most authors have described improvements in neuropsychological functioning on longitudinal testing, related to a normalization of the EEG over time (Callenbach et al, 2010;Baglietto et al, 2001;D'Alessandro et al, 1990;Deonna et al, 2000;Hommet et al, 2001;Lindgren et al, 2004;Metz-Lutz et al, 1999;Northcott et al, 2007;Volkl-Kernstock et al, 2009), but there have also been reports of persistent impairments after remission of the EEG discharges (Monjauze et al, 2005). Although some studies found that the nature of the impairments revealed by neuropsychological testing in BECTS correlated with the side of the epileptic focus (Massa et al, 2001;Piccirilli et al, 1994;Wolff et al, 2005), other studies found no relationship with the BECTS children's performance (Deltour et al, 2007;Vago et al, 2008).…”
Section: Relationship Between Neuropsychological Data and Clinical Fementioning
confidence: 99%
“…The syndrome is apparently benign but only with respect to outcome of seizures (i.e., the child will recover before puberty). In other aspects, a generally favorable prognosis has been questioned, based mainly on a risk for neuropsychological deficits (3)(4)(5)(6)(7)(8). With this background, the term benign should be avoided; RE is preferred.…”
mentioning
confidence: 99%